2014
DOI: 10.3109/10715762.2014.945441
|View full text |Cite
|
Sign up to set email alerts
|

Chronic uranium exposure dose-dependently induces glutathione in rats without any nephrotoxicity

Abstract: Uranium is a heavy metal naturally found in the earth's crust that can contaminate the general public population when ingested. The acute effect and notably the uranium nephrotoxicity are well known but knowledge about the effect of chronic uranium exposure is less clear. In a dose-response study we sought to determine if a chronic exposure to uranium is toxic to the kidneys and the liver, and what the anti-oxidative system plays in these effects. Rats were contaminated for 3 or 9 months by uranium in drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Similarly, none of the clinical markers assessed in plasma and urine samples, including ions and kidney markers (data not shown), revealed any significant differences that might reflect either a significant metabolic disorder or an adverse health effect associated with these NU exposure conditions. A mean NU concentration in kidney tissue less than 500 ng.g À1 (data not shown) confirmed its tubular accumulation in the chronically contaminated rats and, as previously reported, its non-nephrotoxic level, confirmed by histological observations (Leggett 1989;Dublineau et al 2014;Poisson et al 2014). Moreover, for 1.6 g of kidney mass, the absorbed dose rate in the kidneys of the contaminated rats, was estimated at 9 months of age at 5.4 9 10-7 Gy d-1.…”
Section: Clinical Monitoringsupporting
confidence: 86%
“…Similarly, none of the clinical markers assessed in plasma and urine samples, including ions and kidney markers (data not shown), revealed any significant differences that might reflect either a significant metabolic disorder or an adverse health effect associated with these NU exposure conditions. A mean NU concentration in kidney tissue less than 500 ng.g À1 (data not shown) confirmed its tubular accumulation in the chronically contaminated rats and, as previously reported, its non-nephrotoxic level, confirmed by histological observations (Leggett 1989;Dublineau et al 2014;Poisson et al 2014). Moreover, for 1.6 g of kidney mass, the absorbed dose rate in the kidneys of the contaminated rats, was estimated at 9 months of age at 5.4 9 10-7 Gy d-1.…”
Section: Clinical Monitoringsupporting
confidence: 86%
“…21 Recently, a chronic uranium exposure study reported that no nephrotoxic effect was found at kidney uranium concentration 6 lg/g of kidney. 22 We observed that the concentration of uranium retained in kidney tissue after administration of UN varies depending on the dose of UN administrated. Animals dosed with, 4 mg/kg of UN after 3 and 5 d retained high levels of uranium in kidney compared with 2 mg/kg of UN and no detectable amount of uranium was found after 14 and 28 d in 2 mg/kg of UNtreated animals.…”
Section: Concentration Of Uranium In Kidney Tissuementioning
confidence: 86%
“…This observation could be documented by a lesser binding to the macromolecules within the cytoplasm (Bresson et al, ; Frelon, Mounicou, Lobinski, Gilbin, & Simon, ; Ortega et al, ; Perrin, Carmona, Roudeau, & Ortega, ). In addition, we have previously shown from in vivo experiments i using SIMS microscopy that uranium is heterogeneously distributed in the nephron and localized mainly in cell nuclei of proximal convoluted tubules (Poisson et al, ; Tessier et al, ). Similar uranium distribution has been observed using different imaging technic in case of acute renal contamination in rats (Homma‐Takeda et al, ).…”
Section: Discussionmentioning
confidence: 99%